2023
DOI: 10.1101/2023.03.07.531538
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ROS-dependent palmitoylation is an obligate licensing modification for GSDMD pore formation

Abstract: Gasdermin D (GSDMD) is the common effector for cytokine secretion and pyroptosis downstream of inflammasome activation by forming large transmembrane pores upon cleavage by inflammatory caspases. Here we report the surprising finding that GSDMD cleavage is not sufficient for its pore formation. Instead, GSDMD is lipidated by S-palmitoylation at Cys191 upon inflammasome activation, and only palmitoylated GSDMD N-terminal domain (GSDMD-NT) is capable of membrane translocation and pore formation, suggesting that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 47 publications
(78 reference statements)
1
16
0
Order By: Relevance
“…The same residue has recently been proposed to undergo palmitoylation to facilitate membrane association and full activation 61,62 .…”
Section: Discussionmentioning
confidence: 99%
“…The same residue has recently been proposed to undergo palmitoylation to facilitate membrane association and full activation 61,62 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown, that this process is regulated by cellular redox state. Elevated reactive ROS levels may lead to promotion of GSDMD palmitoylation and activation 139 . It can be suggested that the main role of Regulator–Rag in pyroptosis is regulation of ROS and other stimuli that promote ROS production would promote GSDMD oligomerization independently of the Regulator–Rag complex activity 138 …”
Section: Gasdermin Family and Their Role In Programmed Cell Deathmentioning
confidence: 99%
“…Elevated reactive ROS levels may lead to promotion of GSDMD palmitoylation and activation. 139 It can be suggested that the main role of Regulator-Rag in pyroptosis is regulation of ROS and other stimuli that promote ROS production would promote GSDMD oligomerization independently of the Regulator-Rag complex activity. 138 Studies have shown that GSDM family members are involved in pyroptotic and apoptotic pathways.…”
Section: Gasdermin Family and Their Role In Programmed Cell Deathmentioning
confidence: 99%
“…Besides extrinsic membrane features, bGSDMs appear to broadly utilize intrinsic properties such as palmitoylation to strengthen membrane interactions and induce membrane disorder to lower the energy barrier for pore formation. Building on the identification of bGSDM palmitoylation 15 , two recent studies describe a requirement of enzyme-dependent palmitoylation of human and mouse GSDMD for pore formation in cells 32,33 . Though the palmitoylated cysteine (C191 in humans) is located within the fingertip region instead of on the thumb in bGSDMs, we suggest that our model for palmitoyl membrane insertion may explain why the modification is conserved across the tree of life.…”
Section: Mainmentioning
confidence: 99%